The Classification of Contemporary Political Elites - M. A. Amurov (Управленческое консультирование)
The purpose of the article is classification of contemporary political elites. The main steps to achieve this goal are to study the prerequisites for the emergence of the political elite as such, to consider the essence of the political elite in a state, to classify approaches to the definition of the political elite, to define the key types of political elites of today. The method of research is generalized theoretical analysis and systematization. The conducted theoretical analysis has defined the research question and problem: if the formal and conceptual contours of the political elite are approximately the same, but at the same time historical and modern state formations empirically demonstrate the different «power» and «weight» of the elite group, then what is the relevant typology of political elites, which allows predicting the priorities of its development in the future? The author has analyzed five existing classifications of political elites and proposed his own classification. As a result of the research, a new approach to the typology of elites was proposed. In particular, the identification of organizational, communicative, strategic and integration elites in the modern state is justified. This classification describes the functional-role content of elite groups and makes it possible to make an assumption about the development trends of political elites in modern society. The article concludes that the political elite is a society of people who have superiority over the others, and therefore are the most authoritative and competent in matters of state governance. The political elite consists of people who are actively involved in politics and have distinctive features: the right to nominate political leaders from their circles; special privileges; a certain degree of closeness to the elite members of other social strata; thinking based on the psychology of superiority over others; unique ideology; access to confidential state information.